2018
DOI: 10.1055/s-0038-1676105
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Observational Study of Frozen Shoulder among Patients with Diabetes Mellitus

Abstract: Purpose  This study aims to identify the prevalence of frozen shoulder (FS) among diabetic patients and its relation to demographic features. Methods  This observational study of 216 patients randomly included those with diabetes mellitus (DM) attending the Misan Rheumatology and Medical Rehabilitation Department at Al-Sadder Teaching Hospital in Misan Province of Iraq and was conducted during the period from April 2014 to March 2015. Detailed medical histories were taken from patients and scratch test and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 17 publications
(30 reference statements)
2
14
0
1
Order By: Relevance
“…The missing association between lipid values and FS in T1D together with the results on HbA1c and microvascular diseases might indicate that BMI is strongly associated with FS in the general population than in T1D patients, in which other mechanisms such as the accumulation of AGEs might be more important. This is in line with another report of a normal distribution of BMI among diabetes patients with FS 31 . In T2D, higher LDL and total cholesterol levels in patients with FS along with the lack of association with HbA1c might suggest mechanisms that are more comparable to those in the general population.…”
Section: Discussionsupporting
confidence: 93%
“…The missing association between lipid values and FS in T1D together with the results on HbA1c and microvascular diseases might indicate that BMI is strongly associated with FS in the general population than in T1D patients, in which other mechanisms such as the accumulation of AGEs might be more important. This is in line with another report of a normal distribution of BMI among diabetes patients with FS 31 . In T2D, higher LDL and total cholesterol levels in patients with FS along with the lack of association with HbA1c might suggest mechanisms that are more comparable to those in the general population.…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of ACoS in the general population has been estimated to be between 2% and 4%, and it is reported to be significantly higher in patients with diabetes, with estimates ranging from 10% to 22% [10,11]. The rates of ACoS in patients with diabetes 1-5 and 5-10 years after diagnosis were 32.3% and 33.8%, respectively [12]. Huang et al reported a hazard ratio of ACoS development in patients with diabetes compared with those without diabetes was 1.321, after adjusting for age, sex, and dyslipidemia [13].…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely-accepted by some experts that the treatment of diabetic patients with FS compared to that of idiopathic FS is more difficult and they show more resistance to treatment [15][16][17][18][19][20][21][22][23]. However, there have been few well-designed studies of natural history of diabetic FS and comparison of clinical outcomes between diabetic FS and idiopathic FS after conservative treatments [14,24].…”
Section: Discussionmentioning
confidence: 99%